Direction Mapping for Dim-Sighted People - Agrawal, Anshul; Dwivedi, Vaibhav; Brindha R, (International Journal of Psychosocial Rehabilitation, 2020)
The smart walking stick helps blind people to perform navigation and to Complete their work easily and in a comfort way. In normal stick, the detection and recognition of the obstacle is not done and normal stick is not efficient for dim sighted people .Because the blind person is unaware of what type of things or what type of the obstacles come in front of them. The person cannot recognize what is the size of that object and how far is he/she from the object. It is difficult for blind person to move here and there. In smart walking stick, the object is detected with the help of a camera and also it measures the distance between objects by using ultrasonic sensor. If any obstacle or personcomes in front of blind person, he/she can know about that by hearing the sound generated by the ear phones. In this GPS module will also be attached which will enable a person to reach nearby destination with a shorter path. We will try to implement this using Raspberr Pi and using different algorithm that are NEO-6M(NMEA) and OPENCV for better output precision.